The Implementation of Duolingo Mobile Application in English Vocabulary Learning - Ari Irawan; Agus Wilson; Sutrisno Sutrisno (Scope : Journal of English Language Teaching, 2020)
The purposes of this research are as follows: to obtain data and to analyze the effects of the implementation of Duolingo mobile application in English vocabulary. The research was held at SDN 02 Ciputat. All data variables were taken through tests. For vocabulary mastery tests, the data was taken in the questionnaires form. The method used was to conduct a system quality test (Software Quality Assurance) of software quality based on the factors and the criteria established. The data shows that the application gets a score with a pretty good predicate (73,8%), so learning media using the Duolingo mobile application can be applied especially for students in understanding English.